PENERAPAN PENDIDIKAN BERBASIS MULTIKULTURAL - Kumalasari , Nimas; ubab, Ubabuddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
School is an educational institution that prepares students to become generations who have knowledge, insight or attitudes and actions in the life of the nation and state that pay attention to multiculturalism. The diversity of the Indonesian nation which has differences in culture, ethnicity, race, religion can be used as a synergistic source of strength in building the progress of the nation and state.This study uses qualitative research. This means that the data collected is not in the form of numbers, but the data comes from interview transcripts, field notes, personal documents, memo notes, and official documents.. The results of the research stated that in developing multicultural education in schools, several good strategies could be used in teaching and learning activities. Multicultural education is a progressive approach to transforming education which holistically provides criticism and points out weaknesses, failures and discrimination in the world of education. Multicultural education encourages schools to play a role in instilling awareness in a multicultural society and developing an attitude of tolerance and tolerance to realize needs and the ability to work together with all the differences that exist.